Job satisfaction in Finland: Some results from the European Community household panel 1996 - 2001 - Edvard Johansson (The Research Institute of the Finnish Economy (ETLA), 2004)
In this paper we investigate several determinants of job satisfaction using the Finnish part of the European Community Household Panel. In general, Finnish research on job satisfaction using economics methodology is very scarce. Therefore, the paper starts by investigating several “classic” determinants of individual job satisfaction, such as the effect of wage, age, gender, education etc., on job satisfaction. The results of these investigations reveal that the Finnish results look rather similar to the bulk of international results, in the sense that women, those with higher wages, those with low education and so on have higher job satisfaction. We also find that a low level of job satisfaction can predict quits, in line with the international evidence. Further investigations into newer issues reveal that involuntary part-time is associated with lower job satisfaction, and that on-the-job training is associated with higher job satisfaction. – – Tässä paperissa tutkitaan työtyytyväisyyteen vaikuttavia tekijöitä käyttäen European Community Household Panel-aineistoa koskien Suomea. Taloustieteellisestä näkökulmasta tehtyjä suomalaisia tutkimuksia työtyytyväisyydestä on verrattain vähän. Tästä syystä tutkitaan paperissa ensin miten ”perinteiset” tekijät kuten palkkataso, ikä, sukupuoli, koulutustaso vaikuttavat työtyytyväisyyteen. Nämä tekijät ovat ”perinteisiä” siinä mielessä että aikaisemmissa, kansanvälisissä tutkimuksissa, on jo havaittu niiden vaikuttavan työtyytyväisyyteen. Tämän tutkimuksen tuloksien valossa Suomi ei näytä poikkeavan paljon muista maista, koska naisilla, huonommin koulutetuilla, ja korkeapalkkaisilla on muita korkeampi työtyytyväisyys samalla tavoin kuin ulkomailla. Matala työtyytyväisyys myös lisää todennäköisyyttä että työntekijä irtisanoutuu työstään. Paperissa tutkitaan myös työtyytyväisyyteen vaikuttavia tekijöitä, joiden vaikutuksista tiedetään vielä varsin vähän. Henkilöillä, jotka tekevät omasta tahdosta riippumatta osa-aikatyötä on muita matalampi työtyytyväisyys. Tulokset viittaavat myös siihen, että yrityksen tarjoama koulutus nostaa työntekijöiden työtyytyväisyyden.
Keywords: J22; J24; J28; 330; Job satisfaction; quits; part-time work; on-the-job training; Työtyytyväisyys; irtisanoutuminen; osa-aikatyö; henkilöstökoulutus; Arbeitszufriedenheit; Teilzeitarbeit; Betriebliche Weiterbildung; Panel; Finnland